2023
DOI: 10.3390/jcm12113629
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Utilization of Validated Diagnostic Predictive Tools and D-Dimer in the Evaluation of Pulmonary Embolism: A Single-Center Retrospective Cohort Study from a Public Hospital in New York City

Amrin Kharawala,
Jiyoung Seo,
Diego Barzallo
et al.

Abstract: Introduction: A significant increase in the use of computed tomography with pulmonary angiography (CTPA) for the diagnosis of pulmonary embolism (PE) has been observed in the past twenty years. We aimed to investigate whether the validated diagnostic predictive tools and D-dimers were adequately utilized in a large public hospital in New York City. Methods: We conducted a retrospective review of patients who underwent CTPA for the specific indication of ruling out PE over a period of one year. Two independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Gotta et al [ 7 ] found that plasma D-dimer levels were significantly higher in patients with cancer than in healthy participants. Kharawala et al [ 8 ] found that plasma D-dimer levels in patients with esophageal cancer were related to the number of lymph node metastases. Several clinical reports have examined the relationship between pre-operative D-dimer levels and esophageal cancer stage; moreover, elevated D-dimer levels can be seen in venous thrombotic diseases, pulmonary embolism, infectious diseases, and pregnancy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gotta et al [ 7 ] found that plasma D-dimer levels were significantly higher in patients with cancer than in healthy participants. Kharawala et al [ 8 ] found that plasma D-dimer levels in patients with esophageal cancer were related to the number of lymph node metastases. Several clinical reports have examined the relationship between pre-operative D-dimer levels and esophageal cancer stage; moreover, elevated D-dimer levels can be seen in venous thrombotic diseases, pulmonary embolism, infectious diseases, and pregnancy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%